2013
DOI: 10.1080/01425692.2013.814532
|View full text |Cite
|
Sign up to set email alerts
|

How does homework ‘work’ for young children? Children’s accounts of homework in their everyday lives

Abstract: Homework is an increasing yet under-researched part of young children's everyday lives. Framed by the international agendas of starting strong and school accountability, homework in the lives of young children has been either overlooked or considered from the perspective of adults rather than from the perspective of children themselves. This paper redresses this situation by reporting on an Australian study of 120 young children, aged four to eight years, where homework emerges as a key part of their everyday … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Valle, et al (2016) found a positive relationship between school achievement and the homework quantity, time management being related to homework quantity, type of approaching homework being related to time management. Other researchers connected homework quantity to characteristics such as family's socio-economic level; motivation to learn (Rønning, 2010;Dettmers, Trautwein, & Ludke, 2009) and parent's involvement while doing homework (Farrell & Danby, 2013;Margolis, 2015). Rudman (2014) claimed over the fact that homework is not investigated sufficiently.…”
Section: Context and Review Of Literaturementioning
confidence: 99%
“…Valle, et al (2016) found a positive relationship between school achievement and the homework quantity, time management being related to homework quantity, type of approaching homework being related to time management. Other researchers connected homework quantity to characteristics such as family's socio-economic level; motivation to learn (Rønning, 2010;Dettmers, Trautwein, & Ludke, 2009) and parent's involvement while doing homework (Farrell & Danby, 2013;Margolis, 2015). Rudman (2014) claimed over the fact that homework is not investigated sufficiently.…”
Section: Context and Review Of Literaturementioning
confidence: 99%
“…The findings in the area of the parent's involvement in home preparation compared in foreign researchers, e.g., Carvalho (2001) Farrell, & Danby (2015), argue that: -parents become involved in home preparation because they think that it helps their child succeed at school; -parents become involved in home preparation because they care about the future of their child and his/her future education; -parents consider home preparation to be an emotional, relationship, communicational and, most importantly, time investment into the education of their child, often accompanied by negative behavioral aspects (stress, time pressure, inability or impossibility to help their child); -parents do not dispute the role of home preparation, they consider it as natural and obligatory arising from their role of the parent.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Homework is referred to here in the same manner as Farrell and Danby (2015) described: "school-prescribed tasks undertaken by children and usually under the supervision of an adult, most often a parent/parents within the home" (p. 250). "Homework is one of the recurrent activities in the lives of children" (Wingard & Forsberg, 2009, p. 1576, with some researchers reporting that it holds parents and children captive, to the extent that they can no longer develop family priorities and explore interests (Gill & Schlossman, 2004;Kralovec & Buell, 2000).…”
Section: How Homework Shapes Family Literacy Practicesmentioning
confidence: 99%